Application of profit and loss sharing modes in trade financing for small-scale businesses: an alternative to debt Based financing - Sadique, Muhammad Abdurrahman (International Islamic University Malaysia, 2015)

(untitled)
The current article analyses the application of Islamic financing modes based on equity participation for small and medium scale enterprises in short-term trade financing. In lieu of debt based modes such as murabahah favoured by Islamic banks in trade financing, the application of musharakah based alternatives is explored, with especial attention to practical aspects of relevance from a shari‘ah perspective arising in their implementation. Financing goods ready for sale, and financing purchase of stock are examined, comparing the joint-equity based structure with the debt-based structures, and identifying issues of importance. The equity based approach being applied as an all-embracing scheme encompassing purchase of raw material or trade goods to their final sale could be a viable and fairer alternative to debt based financing methods in vogue currently. Adopting suitable equity based structures, especially in the context of short-term financing for small-scale businesses, may provide considerable efficiency and convenience without the involvement of the drawbacks inherent to debt financing structures. Eliminating elements of debt financing from the equity-based modes so as to reveal their full potential and to realize their socioeconomic objectives requires further study and continuous fine-tuning of the modes proposed.